2011
DOI: 10.1165/rcmb.2010-0384oc
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of MUC18 in Airway Epithelial Cells by IL-13

Abstract: Airway bacterial infections are a major problem in lung diseases, including asthma, chronic obstructive pulmonary disease (COPD), and cystic fibrosis. Increased Th2 cytokines, such as IL-13, are observed in lung diseases and may contribute to bacterial infections. How Th2 cytokines affect bacterial infection remains unknown. MUC18, an adhesion molecule shown to be involved in the pathogenesis of malignant melanoma, has been recently identified in airway epithelial cells of patients with COPD. We investigated M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 33 publications
2
26
0
1
Order By: Relevance
“…A previous study suggests up-regulation of MUC18 expression in brushed bronchial epithelial cells from COPD patients [24], but MUC18 function in the lung remains unclear. We have found MUC18 up-regulation in airway epithelial cells as well as in lung macrophages from human asthmatics and COPD patients [13,14]. Importantly, we demonstrated a pro-inflammatory function of MUC18 in lung macrophages in the context of bacterial (e.g., mycoplasma) infection [14].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A previous study suggests up-regulation of MUC18 expression in brushed bronchial epithelial cells from COPD patients [24], but MUC18 function in the lung remains unclear. We have found MUC18 up-regulation in airway epithelial cells as well as in lung macrophages from human asthmatics and COPD patients [13,14]. Importantly, we demonstrated a pro-inflammatory function of MUC18 in lung macrophages in the context of bacterial (e.g., mycoplasma) infection [14].…”
Section: Discussionmentioning
confidence: 89%
“…However, MUC18 regulation and function in inflammatory lung diseases such as asthma or COPD are poorly understood. Our recent publications [13,14] demonstrated MUC18 up-regulation in airway epithelial cells of asthmatics and COPD patients. Importantly, MUC18 is critical to bacteria-induced lung inflammation, which is in part through activation of NF-κB signaling [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serine and threonine are sites of O-linked glycosylation for the peptide backbone [28,29]. From the 22 known human mucin genes 16 mucins genes are expressed in the lung, of which Muc1, Muc4, Muc5AC, Muc5B, and Muc16 reveal the highest expression profiles [30][31][32][33][34]. There are two different types of mucins, the membrane-tethered mucins like Muc1, Muc4, and MucC16, which contribute to the periciliary layer, and the secreted gel-forming mucins like Muc5AC and Muc5B, which form the upper gel-layer and determine the mucus viscosity [28,[35][36][37].…”
Section: Journal Of Clinical and Cellular Immunologymentioning
confidence: 99%
“…Sympathetic nerves release the catecholamine noradrenaline (NA). Catecholamines bind to adreno-MUC5AC, MUC5B, MUC7, MUC8, MUC11, MUC13, MUC15, MUC16, MUC18, MUC19, MUC20, MUC21, and MUC22) mucin genes are expressed (19,31,35,56,63,68). The predicted amino acid sequences of the cloned mucin genes revealed that there are 2 types of mucin groups in humans: secreted and membrane-tethered mucins.…”
Section: +mentioning
confidence: 99%